(untitled) (Acta Scientiarum. Agronomy, 2025)
Several high-density pecan orchards have exhibited unsatisfactory growth and production due to excessive shading. This study aimed to investigate hedge and central pruning and tree thinning as alternative solutions to increase the vegetative growth and production of pecan trees in high-density orchards. The experiment was conducted in Santa Rosa, Rio Grande do Sul State, Brazil, using a randomized block design with three replicates, each consisting of five trees. Treatments included: i) control (no treatment), ii) hedge pruning, iii) central pruning, and iv) tree thinning (tree removal). We evaluated vegetative growth, the number of dry branches, and aspects related to production and production efficiency. Tree thinning resulted in increased transverse width, canopy volume, and the number of basal branches, along with a decrease in dry branches per tree. Production was higher in trees subjected to thinning (78,22%), followed by central pruning (39.80%) and hedge pruning (37.03%), compared to the control. The average yield was higher than the control after both pruning methods; hedge and central pruning increased yield by 37.20 and 39.85%, respectively. However, tree thinning decreased yield by 10.80%. Trees subjected to hedge pruning achieved higher production efficiency relative to canopy volume than the control, while, concerning trunk cross-sectional area, tree thinning was more efficient than the control. Tree thinning increases vegetative growth, production, and production efficiency, while hedge pruning and central pruning lead to higher yields.